PENGARUH KINERJA LINGKUNGAN DAN PROFITABILITAS TERHADAP PENGUNGKAPAN ISR - Fitri Yani; Maulana Yusuf; Badaruddin (EKSYA : Jurnal Ekonomi Syariah, 2022)
This study aims to determine whether there is an influence between environmental performance and profitability on Disclosures Islamic Social Reporting in mining companies listed on the Indonesia Sharia Stock Index in 2017-2019. The population in this study were 27 companies and in this study used purposive sampling technique so that the final sample in this study was 21 companies multiplied by 3 periods to become 63 samples. This study uses data analysis consisting of descriptive analysis, classical assumption test and hypothesis testing assisted by the application of SPSS 21 Statistics. The results show that partially environmental performance affects the disclosure of Islamic Social Reporting while Profitability does not affect the disclosure of Islamic Social Reporting. This study also shows that simultaneously environmental performance and profitability affect the disclosure of Islamic Social Reporting. This study also shows that simultaneously environmental performance and profitability affect the disclosure of Islamic Social Reporting.